Accelerated matrix-vector multiplications for matrices involving genotype covariates with applications in genomic prediction - Freudenberg, Alexander; Vandenplas, Jeremie; Schlather, Martin; Pook, Torsten; Evans, Ross; Ten Napel, Jan (Frontiers in Genetics, 2023)
In the last decade, a number of methods have been suggested to deal with large amounts of genetic data in genomic predictions. Yet, steadily growing population sizes and the suboptimal use of computational resources are pushing the practical application of these approaches to their limits. As an extension to the C/CUDA library miraculix, we have developed tailored solutions for the computation of genotype matrix multiplications which is a critical bottleneck in the empirical evaluation of many statistical models. We demonstrate the benefits of our solutions at the example of single-step models which make repeated use of this kind of multiplication. Targeting modern Nvidia ® GPUs as well as a broad range of CPU architectures, our implementation significantly reduces the time required for the estimation of breeding values in large population sizes.